An??lise da influ??ncia dos conflitos organizacionais na efic??cia do sistema de gest??o ambiental - Bartholomeu Filho, Jaime (2015)
The present study aimed to investigate how the management of the organizational conflicts and aspects of human resource management, such as: empowerment, feedback and performance appraisal rewards and the commitment of management into the organizations affects the effectiveness of the Environmental Management System (EMS). A bibliography study was done about these subjects, and it was noticed that scientific papers, dealing with the subject about conflict within organizations, as part of environmental management are not extensive. This study was based on the study??? Kaur (2011 a, b), with the constructs: return and evaluation, management commitment, empowerment and rewards, adding to it the construct of conflict management, in order to look for relations among them and the effectiveness of the environmental management system. It was developed a questionnaire (survey) based on the used in the studies of Kaur (2011 a, b), adding to it the statements relating to the conflict management construct. The statements were technically evaluated and validated for twenty-one experts and semantically by eight potential answers. The survey was sent by internet, 120 responses received were validated and used for the analysis of two structural models developed based on theoretical grounding and analyzed by SEM methodology - Structural Equation Modeling, with estimation via PLS - Partial Least Squares, not only with the specific data related with the observable variables of each construct, but also evaluating the categorical variables and the existence of moderating variables. The search confirmed to have a relationship between the management's commitments to the effectiveness of the environmental management system, confirming the findings of Kaur (2011 a, b). The adding of the conflict management construct, unprecedented in similar studies resulted, demonstrated the existence of a significant relationship with the construct effectiveness of the environmental management system. It has been shown as the convenient management of the conflicts into the organizations, using the relationship between the exercise of leadership authority, when properly conducted, can influence positively and significantly the effectiveness of the environmental management system, and this aspect a contribution to the practice in the implementation of environmental management systems in organizations.